Prevalence of Malaria among Adults in Ethiopia: A Systematic Review and Meta-Analysis - Fasil Adugna Kendie; Tamirat Hailegebriel W/kiros; Endalkachew Nibret Semegn; Melaku Wale Ferede (Journal of Tropical Medicine)
Background. Malaria is one of the leading causes of mortality and morbidity in tropical and subtropical regions. The bulk of the global malaria burden is in sub-Saharan African countries, including Ethiopia. Malaria adversely affects the health of the peoples as well as the economic development of many developing countries including Ethiopia. Methods. This review article was reported according to PRISMA guidelines. Related published articles were searched from online public databases, such as PubMed, Google Scholar, and ScienceDirect. The search approach used to retrieve related articles were “prevalence,” “malaria,” “adults,” and “Ethiopia.” The quality of articles was assessed using Joana Brigg’s Institute (JBI) critical appraisal checklist. The meta-analysis was computed using STATA version 14. The pooled prevalence estimates with 95% confidence interval were analyzed using a random-effect model, and the possible source of heterogeneity across studies was indicated through subgroup analysis, inverse of variance (I2), and time series analysis. The presence of publication bias was evaluated using funnel plots and Egger’s regression test. Results. Out of 144 studies collected, only eight full-text articles were screened and included in the final quantitative meta-analysis. The pooled prevalence of malaria among adults in Ethiopia was 13.61%. Subgroup analysis based on types of malaria cases showed that the prevalence of malaria among symptomatic and asymptomatic adults was 15.34% and 11.99%, respectively. Similarly, regional subgroup analysis showed that the highest malaria prevalence was recorded in Southern Nations, Nationalities, and Peoples’ Region (SNNPR) (16.17%) followed by Oromia Regional State (13.11%) and Amhara Regional State (12.41%). Discussion and Conclusion. The current systematic review and meta-analysis showed that the pooled prevalence of malaria among adults was found to be greater than the general population and nearly equal to pregnant women. Therefore, the current prevention and control measures, which are related to both vectors and parasites, should be strengthened.